THE EFFECT OF OVARIECTOMY ON WOMEN’S PERIODONTAL STATUS: A PILOT STUDY - Sohail, Kanwal; Zafar, Mahrukh; Zulfiqar, Maham; Kiyani, Amber (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the effect of bilateral oophorectomy on the periodontal status of otherwise healthy women when compared with normal controls. Study Design: Mixed-method study. Place and Duration of Study: Riphah International University, Islamabad, from Apr to Sep 2016. Methodology: A total of 24 women with and without oophorectomy procedures were recruited. Twelve women who has undergone radical hysterectomies at least 6 months prior to the evaluation were recruited for this investigation. These women underwent a comprehensive oral examination with detailed documentation of their periodontal status following a thorough medical/dental history. An age- and sex-matched control population underwent a similar examination. Results: Statistically significant results were noted for probing, color, consistency, texture and contour of gingiva with the p-value of 0.007, 0.001, 0.002, 0.005 and 0.037 when the results were compared with the control population. Conclusion: Bilateral oophorectomy does not compromise the periodontal health of otherwise healthy women.